1992
DOI: 10.1016/0248-4900(92)90211-i
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the heterocellular epidermis of Pelobates syriacus integument

Abstract: Changes in characteristic components of the skin epidermis of the large tadpole of Pelobates syriacus were studied throughout its development. The fate of two specific cells in the skin epidermis was followed, from the young tadpole to the adult was studied. It was found that flask-shaped type cells in the tadpole epidermis which are PAS-positive, stain with peanut lectin (PNA). There is no detectable band 3 in the premetamorphosed stages, and mitochondria-rich cells are very rare. This pattern of staining cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It was found that band 3 protein, assumed to be involved in anion exchange across red cell membranes, and which is localized in renal intercalated (Verlander et al, 1988) and toad MR cells (Devuyst et al, 1993), is expressed only in the MR-like cells of the integument in the larval stage. No binding of these antibodies (mono-or polyclonal) was detected in MR cells of the adult skin, similar to a previous observation that was made on an anuran (Pelobates syriacus; Gabbay et al, 1992). CA I was detected only in the larval skin MR-like cells, while the isozyme CA II was detected both in the larvae MR-like and the adult MR cells.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that band 3 protein, assumed to be involved in anion exchange across red cell membranes, and which is localized in renal intercalated (Verlander et al, 1988) and toad MR cells (Devuyst et al, 1993), is expressed only in the MR-like cells of the integument in the larval stage. No binding of these antibodies (mono-or polyclonal) was detected in MR cells of the adult skin, similar to a previous observation that was made on an anuran (Pelobates syriacus; Gabbay et al, 1992). CA I was detected only in the larval skin MR-like cells, while the isozyme CA II was detected both in the larvae MR-like and the adult MR cells.…”
Section: Discussionsupporting
confidence: 90%
“…Their positive staining with UEA 1 and SBA was similar to that of adult flask cells. However, in another species, Pelobates syriacus, larval flask-like cells (but not adult cells) stained strongly with PNA (Gabbay et al, 1992;Katz et al, 2003). Although the general morphology of larval and adult flask cells appears to be similar, additional histochemical and physiological studies are needed to determine if these cells may be classified as a single cell type.…”
Section: Discussionmentioning
confidence: 96%
“…Yet sites of glycoconjugates have been reported in skin (particularly the epidermis) of other anurans by the use of lectins that bind to specific terminal sugar residues of glycoconjugates, e.g., including the ranids R. perezi Villalba and Navas, 1989;Villalba et al, 1993aVillalba et al, ,b, 1994, R. rugosa (Choi et al, 1997), and R. ridibunda and R. pipiens Zaccone et al, 1999). In addition, sites of glycoconjugates have been identified in aquatic Xenopus laevis Genten and Danguy, 1990;Amano et al, 1995;Zaccone et al, 1999) and several species of terrestrial frogs and toads (Budtz and Spies, 1989;Genten and Danguy, 1990;Gabbay et al, 1992;Faszewski and Kaltenbach, 1995;Katz et al, 1997Katz et al, , 2003Zaccone et al, 1999). The few studies carried out on skin of tadpoles involve R. perezi (Villalba and Navas, 1989;Gabbay et al, 1992;Villalba et al, 1993b), R. dalmatina (Faraldi et al, 1996), X. laevis (Amano et al, 1995), Pelobates syriacus (Gabbay et al, 1992;Katz et al, 2003), and Ceratophrys ornata (Faszewski and Kaltenbach, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any studies on lectin binding in larval skin of R. pipiens. However, there are such reports for larval skin of aquatic Xenopus laevis (Amano et al, 1995), semiaquatic Rana perezi (Villalba and Navas, 1989;Gabbay et al, 1992;Villalba et al, 1993), Rana dalmatina (Faraldi et al, 1996), and R. catesbeiana (Kaltenbach and Faszewski, 2002;Kaltenbach et al, 2004), as well as terrestrial Pelobates syriacus (Gabbay et al, 1992;Katz et al, 2003) and Ceratophrys ornata (Faszewski and Kaltenbach, 1995). Moreover, comparisons of lectin binding in skin from different body regions have been made in only a few species, e.g., adult X. laevis , larval and adult C. ornata (Faszewski and Kaltenbach, 1995), and larval and adult R. catesbeiana (Kaltenbach and Faszewski, 2002;Kaltenbach et al, 2004).…”
mentioning
confidence: 99%